2000
DOI: 10.1128/aem.66.6.2385-2391.2000
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships of Cryptosporidium Parasites Based on the 70-Kilodalton Heat Shock Protein (HSP70) Gene

Abstract: We have characterized the nucleotide sequences of the 70-kDa heat shock protein (HSP70) genes of Cryptosporidium baileyi, C. felis, C. meleagridis, C. muris, C. serpentis, C. wrairi, and C. parvum from various animals. Results of the phylogenetic analysis revealed the presence of several genetically distinct species in the genus Cryptosporidium and eight distinct genotypes within the species C. parvum. Some of the latter may represent cryptic species. The phylogenetic tree constructed from these sequences is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
129
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(141 citation statements)
references
References 35 publications
8
129
0
4
Order By: Relevance
“…One sample did not amplify on the 18S rRNA gene. In five lambs and in the goat kid sample C. parvum (genotype 2) was identified, based on a high homology (>96%) with previously published sequences, both for the 18SrRNA gene (Ryan et al, 2003) and for the HSP-70 gene (Sulaiman et al, 2000;Ryan et al, 2003). In one lamb the pig genotype of C. parvum or Cryptosporidium suis (Ryan et al, 2004) was identified (homology > 97%).…”
Section: Resultsmentioning
confidence: 91%
“…One sample did not amplify on the 18S rRNA gene. In five lambs and in the goat kid sample C. parvum (genotype 2) was identified, based on a high homology (>96%) with previously published sequences, both for the 18SrRNA gene (Ryan et al, 2003) and for the HSP-70 gene (Sulaiman et al, 2000;Ryan et al, 2003). In one lamb the pig genotype of C. parvum or Cryptosporidium suis (Ryan et al, 2004) was identified (homology > 97%).…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, the same results were obtained when compared with three genes of C. baileyi Hungarian strain CBAI-1 (GenBank accession numbers: AJ276096 for 18S rRNA gene, AJ310765 for COWP gene and AJ310880 for HSP70 gene) (Data are not shown) [1]. In contrast, these three genes showed less than 91% homology with C. meleagridis genes (GenBank accession numbers: AF112574, AF221537, AF266266, respectively) [13,15,16] (Table 1). In addition, these genes were classified into the same cluster with C. baileyi other than C. meleagridis by phylogenetic analysis (Fig.…”
mentioning
confidence: 51%
“…These partial sequences of 18S rRNA, COWP and HSP70 genes have been deposited in the GenBank database under accession numbers AB116663, AB116664 and AB116665, respectively. The 18S rRNA, COWP and HSP70 genes sequences from the chicken isolate showed nearly 100% homology with those of C. baileyi genes published by Xiao et al [15], Sulaiman et al [13] and Xiao et al [16], respectiv ely (G enB ank a ccessio n nu mb ers: AF 09 34 95 , AF221539, AF266276, respectively) ( Table 1). Furthermore, the same results were obtained when compared with three genes of C. baileyi Hungarian strain CBAI-1 (GenBank accession numbers: AJ276096 for 18S rRNA gene, AJ310765 for COWP gene and AJ310880 for HSP70 gene) (Data are not shown) [1].…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…sp., [Ryan et al, 2008]) was described after oocysts from a koala (Phascolarctos cincereus) were found to be genetically distinct from other described Cryptosporidium species. Cryptosporidium fayeri has since been characterized at 6 loci and described in a red kangaroo (M. rufous), eastern grey kangaroos (M. giganteus), a western barred bandicoot (Perameles bougainville), and a yellow footed rock wallaby (Petrogale xanthopus) (Morgan, Deplazes et al, 1999;Morgan, Monis et al, 1999;Xiao et al, 1999;Sulaiman et al, 2000;Power et al, 2003Power et al, , 2004. More recently, the Cryptosporidium marsupial ge-notype II was described from eastern grey kangaroos (Power et al, 2004).…”
mentioning
confidence: 99%